Blending ICT with Project Based Learning for Effective Teaching and Learning of Mechatronics - Jadhav, P. S.; Mulla, A. M.; Jadhav, P. M. (Journal of Engineering Education Transformations, 2017)
India is a rapidly growing country with its huge economy. As per the Vision 2020 India has a huge demand for product, services and automation.To fulfill this requirement, more number of engineers are required to build innovative solutions. It’s a known fact that engineering graduates have a strategic and long-term impact on productivity, growth in industry and service sectors [8]. To produce sophisticated industrial products and services that are competitive in the global market and to realize the ’Make in India’ dream, India needs a really high number of well trained and extremely qualified engineering graduates. Unfortunately the facts look a bit dismal. Institutions like the IITs, NITs and a few other public and private technical universities are admittedly performing well but the majority of institutes are affiliated to various universities and teach the curriculum developed by the affiliating university.As a result, they lack the incentive of continuous improvement of the quality of teaching and learning and are not geared to adapt to the changing qualification needs of the job market. So, in order to bridge the quality gap in engineering education there is a need of a platform where ICT is effectively used by premier institutes of India to develop and train teachers and students of private and public sector engineering institution through a combined methodology of Project Based Learning which is completely online.